Valuasi Ekonomi Wisata Alam Pantai Dreamland di Kecamatan Kuta Kabupaten Badung - SIRINGO-RINGO, SARAH STEFANI; WIDHIANTHINI, WIDHIANTHINI; SUDARMA, I MADE (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2023)
Economic Valuation of Dreamland Beach Nature Tourism Kuta District Badung Regency. Dreamland Beach is located in the village of Ungasan, Kuta District, Badung Regency. Dreamland Beach has a natural beauty that can be used as a tourist attraction for every visitor. Natural beauty basically cannot be calculated or has no market value, so the importance of economic valuation is carried out. This study aims to identify factors that affect the number of visits to Dreamland Beach and determine the economic value of Dreamland Beach. This research was conducted from February to Mei 2022. The economic valuation method used is the travel cost method using individuals, while the factors that influence the number of visits are determined by multiple linear regression analysis. Data obtained from 100 visitors to the Dreamland Beach tour. The results of the multiple linear regression analysis for the number of Dreamland Beach visits depend on the length of visitors, distance and travel time, as well as the length of time to find the location. The economic value of Dreamland Beach is Rp. 30. 363,362,035, - per year with a consumer surplus-value of Rp. 677,104 per person / visit.